Identification, expression and characterization of the recombinant Sol g 4.1 protein from the venom of the tropical fire ant Solenopsis geminata - Srisong,Hathairat (2018)
Abstract Background: Fire ant venom is a complex mixture consisting of basic piperidine alkaloids, various biologically active peptides and protein components, including a variety of major allergenic proteins. Tropical fire ant Solenopsis geminata is an important stinging ant species that causes anaphylaxis and serious medical problems. Although the biological activities of allergenic venom proteins that are unique to ant venom, particularly Solenopsis 2 and 4, are still unknown, these proteins are believed to play important roles in mediating the effects of the piperidine derivatives in the venom. Methods: In the present study, the cDNA cloning, sequencing and three-dimensional structure of Sol g 4.1 venom protein are described. The recombinant Sol g 4.1 protein (rSol g 4.1) was produced in E. coli , and its possible function as a hydrophobic binding protein was characterized by paralyzing crickets using the 50% piperidine dose (PD50). Moreover, an antiserum was produced in mice to determine the allergenic properties of Sol g 4.1, and the antiserum was capable of binding to Sol g 4.1, as determined by Western blotting. Results: The molecular weight of Sol g 4.1 protein is 16 kDa, as determined by SDS-PAGE. The complete cDNA is 414 bp in length and contains a leader sequence of 19 amino acids. The protein consists of six cysteines that presumably form three disulfide bonds, based on a predicted three-dimensional model, creating the interior hydrophobic pocket and stabilizing the structure. The rSol g 4.1 protein was expressed in inclusion bodies, as determined by SDS-PAGE. Dialysis techniques were used to refold the recombinant protein into the native form. Its secondary structure, which primarily consists of α-helices, was confirmed by circular dichroism analysis, and the three-dimensional model was also verified. The results of allergenic analysis performed on mice showed that the obtained protein was predicted to be allergenically active. Moreover, we report on the possible role of the Sol g 4.1 venom protein, which significantly reduced the PD50 from 0.027 to 0.013% in paralyzed crickets via synergistic effects after interactions with piperidine alkaloids. Conclusions: The primary structure of Sol g 4.1 showed high similarity to that of venom proteins in the Solenopsis 2 and 4 family. Those proteins are life-threatening and produce IgE-mediated anaphylactic reactions in allergic individuals. The possible function of this protein is the binding of the interior hydrophobic pockets with piperidine alkaloids, as determined by the analysis of the structural model and PD50 test.